ANALISIS PENGARUH KOMPETENSI DAN TINGKAT PENDIDIKAN TERHADAP KINERJA KARYAWAN DENGAN BUDAYA ORGANISASI SEBAGAI VARIABEL INTERVENING DI KEBUN SEI MERANTI PT PERKEBUNAN NUSANTARA III - Asfian Nasution; Retna Astuti; Erwin Nyak Akoeb; Angga Dwi Kelana Putra (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
In the plantation sector, such as in large companies like PT Perkebunan Nusantara III (Persero), the competence and educational level of human resources are key pillars for improving the efficiency, productivity, and competitiveness of the company. Competent, trained human resources with an adequate level of education are able to face the challenges of managing and maximising production, which ultimately has an impact on the achievement of organisational targets. Furthermore, competence is a key aspect in solving problems appropriately, combined with educational attainment. In addition, good competence, combined with a supportive organisational culture, significantly increases work productivity. The researcher aims to analyse the influence of competence and education on employee performance through organisational culture. This study utilised a quantitative approach combined with descriptive qualitative data to reinforce the findings through interviews with structural equation modelling data analysis with a sample size of 90 employees. Competence has an indirect effect on employee performance through organisational culture with a value of -0.136. In addition, the level of education also shows a negative indirect effect on employee performance through organisational culture, with a value of -0.113. This study's t-statistics for all variables are able to produce a significant effect and have a very large f² except for the f² of organisational culture (z) on employee performance (y), which has a small effect.